Formal and relational mechanisms of network governance and their relationship with trust: substitutes or complementary in Brazilian real estate transactions?. (16th March 2020) - Carnauba, Adriano Augusto Costa; Boaventura, João Maurício Gama; Pereira, Cristina Espinheira Costa; Azevedo, Ana Cláudia; Todeva, Emanuela
The objective of this study was to investigate whether formal and relational mechanisms of network governance act as substitutes or are complementary in their relationship with trust in the intermediation activity of real estate transactions. We conducted a quantitative study to test the hypotheses. We collected data via a survey and the context was Brazilian real estate business networks. We used a non-parametric approach to investigate the associations among the key variables indicated in the theory. The results confirm the hypothesis that formal and relational mechanisms of network governance act as complementary and reject the possibility of substitution between them. Both mechanisms are important to build trust-based relationships between actors and formal governance mechanisms have a significant positive relationship with inter-organisational trust, while relational mechanisms are positively associated with interpersonal trust. This study not only contributes to the discussion on governance mechanisms and their relationship with trust, but also broadens this debate by considering trust at different levels and in more complex structures where these relationships are still barely explored, such as is the case of business networks.